Prognostic Value of Left Atrial Function in Dogs with Chronic Mitral Valvular Heart Disease - Nakamura, K. (J Vet Intern Med, 2014)
BACKGROUND: A strong correlation between left atrial (LA) dysfunction and the severity of cardiac disease has been described in human patients with various cardiac diseases. The role of LA dysfunction in dogs with chronic mitral valvular heart disease (CMVHD) has not been addressed. OBJECTIVES: To investigate the correlation between LA function and the prognosis of dogs with CMVHD. ANIMALS: Thirty‐eight client‐owned dogs with CMVHD. METHODS: Prospective clinical cohort study. Dogs were divided into 2 groups (survivors and nonsurvivors) based on the onset of cardiac‐related death within 1 year. Physical examination and echocardiographic variables were compared between the groups. For the assessment of the comparative accuracy in identifying patients with cardiac‐related death, receiver operating characteristic (ROC) curves and multivariate logistic analysis were used. RESULTS: The highest accuracy was obtained for the LA active fractional area change (LA‐FAC (act)), with an area under the ROC curve (AUC) of 0.95, followed by the left atrial to aortic root ratio (LA/Ao), with an AUC of 0.94; peak early diastolic mitral inflow velocity (E), with an AUC of 0.85; and LA total fractional area change (LA‐FAC (total)), with an AUC of 0.85. In the multivariate logistic regression analysis, LA‐FAC (act) emerged as the only independent correlate of cardiac‐related death within 1 year (odds ratio = 1.401, P = .002). CONCLUSIONS AND CLINICAL IMPORTANCE: Regarding both the size and function, the LA has a strong correlation with the prognosis of dogs with CMVHD. The most significant independent predictor of mortality in this study was LA‐FAC (act).